A Chromosome-Level Genome Assembly of the Anglerfish Lophius litulon - Lv, Meiqi; Zhang, Yaolei; Liu, Kaiqiang; Li, Chang; Wang, Jiahao; Fan, Guangyi; Liu, Xin; Yang, Huanming; Liu, Changlin; Mahboob, Shahid; Liu, Junnian; Shao, Changwei (Frontiers in Genetics, 2020)
Anglerfishes are a highly diverse group of species with unique characteristics. Here, we report the first chromosome-level genome of a species in the order Lophiiformes, the yellow goosefish (Lophius litulon), obtained by whole genome shotgun sequencing and high-throughput chromatin conformation capture. Approximately 97.20% of the assembly spanning 709.23 Mb could be anchored to 23 chromosomes with a contig N50 of 164.91 kb. The BUSCO value was 95.4%, suggesting that the quality of the assembly was high. A comparative gene family analysis identified expanded and contracted gene families, and these may be associated with adaptation to the benthic environment and the lack of scales in the species. A majority of positively selected genes were related to metabolic processes, suggesting that digestive and metabolic system evolution expanded the diversity of yellow goosefish prey. Our study provides a valuable genetic resource for understanding the mechanisms underlying the unique features of the yellow goosefish and for investigating anglerfish evolution.